ChemInform Abstract: Regioselective Bromination of 1, 4‐Dimethoxy‐2, 3‐dimethylbenzene and Conversion into Sulfur‐Functionalized Benzoquinones. Issue 30 (7th July 2016) - Aitken, R. Alan; Jethwa, Siddharth J.; Richardson, Neville V.; Slawin, Alexandra M.Z.
Abstract: Four different bromination products can be prepared from the starting material (I) including the novel compound (VIII).